Suppressed power saturation due to optimized optical confinement in 9xx nm high-power diode lasers that use extreme double asymmetric vertical designs. (31st January 2018) - Kaul, T; Erbert, G; Maaßdorf, A; Knigge, S; Crump, P
Abstract: Broad area lasers with novel extreme double asymmetric structure (EDAS) vertical designs featuring increased optical confinement in the quantum well, Γ, are shown to have improved temperature stability without compromising series resistance, internal efficiency or losses. Specifically, we present here vertical design considerations for the improved continuous wave (CW) performance of devices operating at 940 nm, based on systematically increasing Γ from 0.26% to 1.1%, and discuss the impact on power saturation mechanisms. The results indicate that key power saturation mechanisms at high temperatures originate in high threshold carrier densities, which arise in the quantum well at low Γ. The characteristic temperatures, T 0 and T 1, are determined under short pulse conditions and are used to clarify the thermal contribution to power limiting mechanisms. Although increased Γ reduces thermal power saturation, it is accompanied by increased optical absorption losses in the active region, which has a significant impact on the differential external quantum efficiency, η diff . To quantify the impact of internal optical losses contributed by the quantum well, a resonator length-dependent simulation of η diff is performed and compared to the experiment, which also allows the estimation of experimental values for the light absorption cross sections of electrons and holes inside the quantum well. Overall, the analysis enables vertical designs to be developed, for devices with maximized power conversion efficiency at high CW optical power and high temperatures, in a trade-off between absorption in the well and power saturation. The best balance to date is achieved in devices using EDAS designs with Γ = 0.54 %, which deliver efficiencies of 50% at 14 W optical output power at an elevated junction temperature of 105 °C.